AN ANALYSIS OF THE TOXIC ACTIONS OF PURIFIED STREPTOLYSIN O ON THE ISOLATED HEART AND SEPARATE CARDIAC TISSUES OF THE GUINEA PIG - Reitz, Bruce A. (The Rockefeller University Press, 1968)
The response of isolated guinea pig hearts to perfusion with purified streptolysin O is characterized by a rapid, but transient, decrease in rate and amplitude of contraction; these reactions are superimposed upon a gradual, irreversible, loss of ventricular contractility. At ventricular standstill, the atria continue to beat spontaneously in a normal way. Isolated ventricle strips prepared from such preparations can be driven electrically, and their behavior is functionally indistinguishable from that of similar preparations made from normal hearts. Tests on spontaneously beating isolated atrial pairs show that the toxin induces a dose-dependent, reversible, decline in rate and amplitude which is accompanied by a marked, but transient, increase in the velocity of repolarization of the intracellular potential. The atrial reactions were completely blocked by atropine and potentiated by eserine. Acetylcholine was detected in the perfusates obtained by incubating a large pool of atrial tissue with active toxin, supporting the inference that the transient mechanical and electrophysiological reactions to toxin might be consequences of the release of acetylcholine from these tissues by the active toxin. Control studies showed that only the active toxin had the capacity to induce the cardiac responses. The toxin was active only in the reduced but not the oxidized form. The effects of the active toxin were modified if it were heated prior to challenge, and they could be neutralized by specific antiserum and inhibited by cholesterol. Since the driven ventricle strip was mechanically and electrophysiologically insensitive to streptolysin O, the irreversible changes in the whole heart must have occurred because of a defect in the atrioventricular conduction system.